Inventory of Rare Fruit in Sibohe Forest of Singkawang City, West Kalimantan - Wolly Candramila; Asriah Nurdini Mardiyyaningsih; Yogi Dirgari; Robby Firmansyah; Muhammad Reza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The location close to urban areas and the rapid rate of decline in area can threaten the diversity of rare fruits in the Sibohe Forest. A re-survey in the Sibohe Forest, Singkawang, West Kalimantan was conducted to confirm reports of the existence of 15 rare fruit plant species collected in 2017-2018 by previous researchers. The inventory process started from collection of specimens carried out during June-July 2021, herbarium making, identification and descriptive data analysis. Based on the similarity of regional names, 13 out of 15 species were confirmed according to the previous reports, while 2 species were not found due to the possibility of out of fruiting season. However, 4 of the 13 confirmed species were identified with different scientific names. Additional survey to the people in Pontianak City aged 17-34 years revealed some different names for the same type of fruit among these four species. Four new plant species were also collected and described in this study including amok (Alpinia sp., Zingiberaceae), nubik (Artocarpus sp., Moraceae), tehengan (Artocarpus sp., Moraceae), and smallest arok (Ficus sp., Moraceae). Potentials and challenges in the inventory of rare fruit plants in the Sibohe Forest should be studied regularly as well as efforts to increase public knowledge and interest, especially for the younger generation. Moreover, recommendation should be made to support conservation activities based on the actual data collected in the field regularly.